Impact of irrigation, nitrogen fertilization, and plant density on stay-green and its effects on agronomic traits in maize - Chibane, Nadia; Revilla, Pedro; Yannam, Venkata Rami Reddy; Marcet, Purificación; Covelo, Emma Fernández; Ordás, Bernardo (Frontiers in Plant Science, 2024)
Introduction The stay-green (SG) or delayed leaf senescence enables crop plants to maintain their green leaves and photosynthetic capacity for a longer time after flowering. It is considered an important trait in maize breeding, which has contributed to gain in grain yield of modern varieties. It has been also used to improve the tolerance to drought and deficiencies in nitrogen fertilization (NF). However, the objective of this study is to evaluate the influence of water irrigation (WI), NF, and plant density (PD) on SG and the effect of SG on agronomic traits in maize. Methods Four SG lines and four non–stay-green (NSG) lines were evaluated in four contrasting environments under two WI, three NF, and two PD levels. Results and discussion As expected, the chlorophyll content of leaves at 45 days after flowering (Chlo45) was, on average, higher in the SG group of lines. The difference in Chlo45 between the SG and NSG genotypes was consistent across WI, NF, and PD and the environments. This is indicative that internal or developmental factors were more important than external signals in controlling the senescence. The effect of SG increasing thousand-kernel weight, stover yield at harvest, or moisture was not influenced by WI, NF, or PD but was altered by the background environment. Our results have implications for the application of SG as a secondary trait for enhancing abiotic stress tolerance. Future studies could consider a wider range of environmental conditions to assess the performance of SG traits under different climatic and soil conditions.